(untitled) (Research, Society and Development, 2020)
Clay masks are considered to be the oldest cosmetic preparations used in beauty treatment due to their wide range of properties, therefore, their applicability in the cosmetic area depends primarily on the chemical and mineralogical composition. This variability in composition reinforces the need to carry out studies that provide a greater understanding of the compounds involved, as well as the different possibilities of applications. The objective was to characterize samples of kaolinite concentrate from the states of Paraíba and Rio Grande do Norte in order to carry out a comparative study with the parameters defined by companies in the segment. To carry out the research, samples were collected in three different kaolin processing units, laboratory tests were carried out following specific methodologies for the cosmetic segment and, later, comparisons with specifications obtained in technical reports. The tests were: moisture determination, screening test, pH determination, absorption test and qualitative colorimetric test. The results obtained showed high humidity values for all samples as a result of the beneficiation process, while in the screening test there was no sample with behavior outside the established limit. The samples were slightly acidic with A2 and A3 showing satisfactory values, whereas in the oil absorption test, samples A1 and A2 met the variation limits. The qualitative colorimetric assay characterized the sample A2 as most suitable for the intended purpose in terms of staining.